Allogeneic FLT3 CAR T Cells with an Off-Switch Exhibit Potent Activity against AML and Can Be Depleted to Expedite Bone Marrow Recovery - Sommer, Cesar (Mol Ther, 2020)
Patients with relapsed or refractory acute myeloid leukemia (AML) have a dismal prognosis and limited treatment options. Chimeric antigen receptor (CAR) T cells have achieved unprecedented clinical responses in patients with B cell leukemias and lymphomas and could prove highly efficacious in AML. However, a significant number of patients with AML may not receive treatment with an autologous product due to manufacturing failures associated with low lymphocyte counts or rapid disease progression while the therapeutic is being produced. We report the preclinical evaluation of an off-the-shelf CAR T cell therapy targeting Fms-related tyrosine kinase 3 (FLT3) for the treatment of AML. Single-chain variable fragments (scFvs) targeting various epitopes in the extracellular region of FLT3 were inserted into CAR constructs and tested for their ability to redirect T cell specificity and effector function to FLT3(+) AML cells. A lead CAR, exhibiting minimal tonic signaling and robust activity in vitro and in vivo, was selected and then modified to incorporate a rituximab-responsive off-switch in cis. We found that allogeneic FLT3 CAR T cells, generated from healthy-donor T cells, eliminate primary AML blasts but are also active against mouse and human hematopoietic stem and progenitor cells, indicating risk of myelotoxicity. By employing a surrogate CAR with affinity to murine FLT3, we show that rituximab-mediated depletion of FLT3 CAR T cells after AML eradication enables bone marrow recovery without compromising leukemia remission. These results support clinical investigation of allogeneic FLT3 CAR T cells in AML and other FLT3(+) hematologic malignancies.